PENYULUHAN PERILAKU HIDUP BERSIH SEHAT (PHBS) DAN KESEHATAN REPRODUKSI REMAJA DI SEKOLAH MADRASAH ALIYAH ALKHAIRAAT BIROMARU - Nur Ani Nur Ani (JOURNAL OF COMMUNITY DEDICATION, 2022)
Cleanliness of the school environment is an important aspect to create a healthy school environment. Because if the environment is healthy then all living things around it will also be able to breathe properly. Especially students will be able to receive lessons well. Because if the classroom is clean then the air will be cool. Therefore the brain will carry out its functions and functions perfectly. Adolescence (age 11-20 years) is a special and important period, because it is a period of maturation of the human reproductive organs. Adolescence is also called puberty, is a unique transition period marked by various physical, emotional and psychological changes. Teenagers are in a situation that is very sensitive to the influence of new values, especially for those who have no deterrent power. They tend to make adjustments more easily to the flow of globalization and the free flow of information which can cause changes in deviant behavior due to adaptation to values that come from outside. The most prominent problem among teenagers today, for example, is sexuality, resulting in getting pregnant out of wedlock and having abortions. With sufficient motivation and knowledge to lead a healthy adolescent life, it is hoped that adolescents will be able to maintain their own health so that they are able to enter a period of family life with healthy reproduction.